Penggabungan Mapbox dan Google Maps dalam Sistem Informasi Geografis untuk Memperkaya Fitur Tambahan - Wiwit Wahyudi (Jurnal Ilmu Komputer Ruru, 2024)
The use of geographic information systems (GIS) is increasingly widespread in various applications that utilize geographic data to support decision making and spatial analysis. In GIS development, integration between various mapping platforms is key to enriching features and meeting diverse user needs. This paper discusses the merger between Mapbox and Google Maps in a geographic information system to add additional features that enrich the user experience. Mapbox and Google Maps are two popular and powerful mapping platforms, each with its own advantages and disadvantages. In this study, we propose the integration of these two platforms in one geographic information system. This integration allows users to access a wide array of features and data provided by Mapbox and Google Maps simultaneously, thereby increasing the flexibility and analytical capabilities of GIS. By combining the strengths of Mapbox and Google Maps, the developed geographic information system can present a variety of geographic information more comprehensively and accurately. Users can benefit from excellent features from both platforms, such as rich and interactive data visualization, accurate navigation, and integration with other services such as public transportation and location search. It is expected that the incorporation of Mapbox and Google Maps in this geographic information system can make a positive contribution in the development of location-based applications and support various activities that require efficient and effective analysis and visualization of geographic data.